PEMBINAAN MASJID PARIPURNA KECAMATAN TAMPAN KOTA PEKANBARU - Anshara, Sari; Mashur, Dadang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
As an effort Pekanbaru government to realize Pekanbaru as a Madani city is to approve the planery mosque as a place for fostering the faith and piety of Pekanbaru city residents whose existence of the plenary mosque itself is increasingly being multiplied by the designation plan at the village level . The problem of coaching is not yet optimal has an impact on aspects of planning that are not yet participatory, slow and not rimely budget disbursement and bugdet accountibility which are difficult to perceive as a factor affecting of the coaching planery mosque at tampan sub- district pekanbaru.This research is examined by using the concept of government coaching with the concept and effectiveness of the organization with fundamental analysis on the implementation of coaching activities and whether or not the activity is measured. This research was designed using a quality approach and descriptive data analysis.This research found that implementation of coaching planery mosque at Tampan sub-district no effective as well. Coaching conducted conditionally has not had a significant impact on the achievement of performance indicators of the plenary mosque program as a forum for fostering the community to reach civil society. The coaching carried out is more focused on the imarah program (prosperous), while idharah (management) and riayah (maintenance and procurement of facilities) have not been taken seriously yet. As for the factors that influence the implementation of the plenery mosque in the tampan sub-district identified in two aspects. First, the aspect seriousness of the government as the owner of the plenery mosque program seriousness in question is that coaching should be used as routine and planned activities. Secondly, the additional aspect of the task is that this guidance is only an additional task for the subdistrict head and other official so that it does not become a priority scale. Keywords : Coaching, Planery Mosque, Pekanbaru